Diseño de un manual de procedimientos contables y tributarios al Supermercado ECOMARKET de la Sra. León Chuqui Viviana Elizabeth de la ciudad de Loja. - Cuenca Merchán, Yeymi Lizbeth (2024)
The Curricular Integration Work called: Design of an accounting and tax procedures manual for the ECOMARKET Supermarket of Mrs. León Chuqui Viviana Elizabeth in the city of Loja was developed with the purpose of providing a guide with policies and procedures to ensure the efficient management of accounting and tax operations. In order to fulfill the objectives set, an interview was conducted with the manager and personnel working in the company. This information was captured in a SWOT analysis matrix that revealed the current situation of the ECOMARKET Supermarket, internal factors such as structure, policies and procedures, and external factors such as political instability and competition that influence the development of the company. Subsequently, accounting policies and procedures were established with their respective formats and standard entries to verify that the operations of current assets: cash and cash equivalents, customer accounts receivable, merchandise inventory; non-current assets: property, plant and equipment; current liabilities: accounts payable to suppliers; non-current liabilities: long-term obligations with financial institutions; revenues: sale of goods; administrative expenses: wages and salaries; selling expenses; and accounting process are executed correctly. Likewise, tax policies and procedures were established to obtain the RUC code and registration, and to prepare the Value Added Tax Return, Income Tax Return, Withholdings at Source, Simplified Transactional Annex and Dependency Relationship Annex in accordance with current regulations and the guidelines of the Internal Revenue Service (Servicio de Rentas Internas). Finally, flow charts of accounting and tax procedures were designed to facilitate management. At the end of the Curricular Integration Work, it was determined that the design of an accounting and tax procedures manual will allow the personnel of the accounting and tax area of the Supermarket to know step by step how to carry out the activities and avoid possible irregularities.